Reliability of KAROSA buses run by a joint‐stock company ‘Vilnius buses’ - Lukoševičius, Kestutis; Lukoševičiene, Nijole; Zaikauskas, Mindaugas (Transport, 2005)
In the paper the data on operating reliability of KAROSA buses run by a joint‐stock company ‘Vilnius buses’ are presented. The pneumatic front suspension and an automatic gearbox are investigated. The failures of these units and their causes are considered and some recommendations to increase the reliability of the equipment are provided. The need for using high‐quality materials in maintaining the vehicles is demonstrated by the study of an actual case of highly corroded bearings.First Published Online: 27 Oct 2010